Building electro-optical systems : making it all work - Hobbs, Philip C. D. (Wiley, 2009)
Updated to include new developments in technology with a new chapter on mechanics and motion, the second edition of 'Building Electro-Optical Systems' presents a systematic approach to electro-optical instrument design and construction.